Barriers to conservative care from patients' and nephrologists' perspectives: the CKD-REIN study. Issue 12 (13th January 2022) - Hamroun, Aghilès; Speyer, Elodie; Ayav, Carole; Combe, Christian; Fouque, Denis; Jacquelinet, Christian; Laville, Maurice; Liabeuf, Sophie; Massy, Ziad A; Pecoits-Filho, Roberto; Robinson, Bruce M; Glowacki, François; et al.
ABSTRACT: Background: Conservative care is increasingly considered an alternative to kidney replacement therapy for kidney failure management, mostly among the elderly. We investigated its status and the barriers to its implementation from patients' and providers' perspectives. Methods: We analysed data from 1204 patients with advanced chronic kidney disease (CKD) [estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m 2 ] enrolled at 40 nationally representative nephrology clinics (2013–16) who completed a self-administered questionnaire about the information they received and their preferred treatment option, including conservative care, if their kidneys failed. Nephrologists ( n  = 137) also reported data about their clinics' resources and practices regarding conservative care. Results: All participating facilities reported they were routinely able to offer conservative care, but only 37% had written protocols and only 5% had a person or team primarily responsible for it. Overall, 6% of patients were estimated to use conservative care. Among nephrologists, 82% reported they were fairly or extremely comfortable discussing conservative care, but only 28% usually or always offered this option for older (>75 years) patients approaching kidney failure. They used various terminology for this care, with conservative management and non-dialysis care mentioned most often. Among patients, 5% of those >75 years reported receiving information about this option and 2% preferring it. Conclusions: Although reported by nephrologists to be widely available and easily discussed, conservative care is only occasionally offered to older patients, most of whom report they were not informed of this option. The lack of a person or team responsible for conservative care and unclear information appear to be key barriers to its implementation.